A integração latino-americana nas escolas latino-americanas de agroecologia da Cloc-Via campesina no Brasil e Venezuela. - Campos, João Carlos de (2014)
This work allows a reflection on the historical process of creation and implementation of the Latin American Schools of Agro-ecology, under the responsibility of CLOC-Via Campesina (Latin American Coordination of Rural Organizations and Via Campesina), as an established strategy to carry on formation of activists to build up the integration of peasants of Latin America. This school project had its begin on the first years of the 21st century. It is rooted in the perspective of Bolivarian Alliance to People of Our America ALBA (Commerce Trade of the People), out of the concept that integration is cooperation, solidary and complementarity. Therefore, the problem in this paper is to analyze how to express the Latin American integration in the curriculum of these schools. From a qualitative analytical approach the general goal of this dissertation was to analyze how the Latin American integration expresses itself in the formation process of the students of the Latin American School of Agro-ecology (ELAA-Brasil) and of the Latin American College Institute of Agro-ecology Paulo Freire (IALA-Paulo Freire/Venezuela), throughout the curricular framing and syllabus of the disciplines. In order to come to true this objective the following specific goals were established: a) to present some aspects of theories that guide the concept of Latin American integration in the region; b) to present the historical process of creation and implementation of the schools of Agro-ecology of the CLOC-Via Campesina in Brasil and Venezuela; c) highlight from the curriculums of those schools listed above the mention of Latin American Integration; d) identify and analyze the concept of integration expressed in the curricular framing and its contends. From the literature, documentary and field research , which was gathered from the Latin American School of Agroecology Cloca - Via Campesina fit into the context of a dispute of class projects with antagonistic content, and express the theoretical orientations of curriculum and content the disciplines that make up the courses , as well as the internationalist character, which are in the opposite direction of the projects that advocate the integration and incorporation of new markets. It is a political , educational and social project that aims to shine their light to the different corners of Latin America, since the subjects trained in Elaa Iala Paulo Freire and return to their countries of origin where they continue to struggle for a decent life for future generations , to build and strengthen a new mode of production oriented to socialism and supported in agroecology , which is linked to the need for an integration that takes place among Latin American countries to constitute a " Patria Grande " Latin America based on values of equality and solidarity.